1996
DOI: 10.1021/jp960280y
|View full text |Cite
|
Sign up to set email alerts
|

Global Analysis of the Fluorescence Decays of N,N‘-Dioctadecyl Rhodamine B in Langmuir−Blodgett Films of Diacylphosphatidic Acids

Abstract: Langmuir-Blodgett multilayer films were prepared from N,N′-dioctadecyl rhodamine B (RB18) diluted in dioleoylphosphatidic acid (DOPA) or dipalmitoylphosphatidic acid (DPPA) with various mixing ratios. Surface pressure-area isotherms of monolayers of the two matrices were recorded. Absorption and fluorescence spectra and fluorescence decays of the multilayer samples of RB18 were further examined. The fluorescence decay curves of RB18 in the multilayer assemblies, determined using time-correlated single photon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
76
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(88 citation statements)
references
References 87 publications
12
76
0
Order By: Relevance
“…), which have many oxidation states, especially their low oxidation states oxides or salts show many potential applications in photochromic devices [57], batteries [58][59][60], pigments [61], conductive medium adding in polymers [62] or as reducing reagents, etc. On the other hand, the RhB molecules show strong fluorescent emission at about 580 nm, thus have been fabricated photofunctional materials with other organic compounds [39,63]. Therefore, the RBMA aggregates with the shape or morphology of sphere nanoparticles, disks, hexagonal rods, networks and branches would also show the fluorescent characteristics of RhB molecules.…”
Section: Photofunctional Properties Of the Rbma Aggregatesmentioning
confidence: 99%
“…), which have many oxidation states, especially their low oxidation states oxides or salts show many potential applications in photochromic devices [57], batteries [58][59][60], pigments [61], conductive medium adding in polymers [62] or as reducing reagents, etc. On the other hand, the RhB molecules show strong fluorescent emission at about 580 nm, thus have been fabricated photofunctional materials with other organic compounds [39,63]. Therefore, the RBMA aggregates with the shape or morphology of sphere nanoparticles, disks, hexagonal rods, networks and branches would also show the fluorescent characteristics of RhB molecules.…”
Section: Photofunctional Properties Of the Rbma Aggregatesmentioning
confidence: 99%
“…In all of these cases, as well as at compression of the monolayers of N,N'-dioctadecyl rhodamine B perchlorate on pure water and on water containing varying concentrations of sodium n-dodecyl sulfate, studied by Slyadneva et al, 36 competition between dye molecules and surfactants in the monolayers is evident. However, in spite of the absorption spectra in Langmuir -Blodgett films 34 and reflection-absorption spectra in solid-condensed monolayers, 36 our above spectral data give no reliable evidence for dimer formation (see above).Tamai et al 16 reported the spectra of N,N'-dioctadecyl rhodamine B perchlorate in mixed Langmuir-Blodgett films with arachidic acid and methylarachidate, obtained on CdCl 2 -containing subphase, while Ballet et al 31 studied the multilayers of the same dye with diacylphosphatidic acid, obtained from monolayers on aqueous CaCl 2 -containing subphase (in several cases alternated by layers of cadmium arachidate). Comparison of our data with those reported by these authors allows to conclude that phase separation during compression of the mixed monolayers, resulting in dimer formation, is not typical for polymer-based system containing n-heptadecyl rhodamine B.…”
mentioning
confidence: 81%
“…31 Each dye-containing monolayer was alternated with three ODA monolayers, prepared on pure aqueous subphase at π = 28 mN m -1 , using the Langmuir trough with two chutes. This allows to attribute the Vis absorption spectrum mainly to the monomeric species of the free rhodamine dye cation or ionic pair with perchlorate anion; the possible dimer formation does not manifest itself markedly, and the 'shoulder' at 520-530 nm is rather of vibrational nature.…”
Section: Dye-containing Polyamic Mono-and Multilayersmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetics of long-range electronic energy transfer between molecular probes dispersed in or chemically bound to micro-heterogeneous systems, like surfactant micelles, polymer coils in solution, micro-emulsions, nano-latex particles, and block copolymer micelles, is recognized as an efficient tool to investigate the morphology of those structures as well as their interactions with solutes at a molecular level [21][22][23][24][25][26][27]. The intrinsic distance dependence of the energy transfer process in the dipole-dipole mechanism gives information on the spatial arrangement of the acceptors around the donor, and therefore insights on the structural aspect and interactions of the nano size host particle.…”
Section: Introductionmentioning
confidence: 99%